Intrathecal Baclofen in Hereditary Spastic Paraparesis - Pucks-Faes, Elke; Dobesberger, Judith; Hitzenberger, Gabriel; Matzak, Heinrich; Mayr, Andreas; Fava, Elena; Genelin, Eleonora; Saltuari, Leopold (Frontiers in Neurology, 2019)
Introduction: Treatment with intrathecal baclofen (ITB) is a therapeutic option in the management of severe spasticity in patients with hereditary spastic paraparesis (HSP). However, information on the impact of ITB on the natural course of disease, especially the effect of ITB on functional parameters over time is limited. Materials and Methods: We evaluated 7 patients with HSP retrospectively who were treated with an ITB device. The following parameters were measured before (pre-implantation) and after implantation (post-implantation) of the ITB device at steady state dosage of ITB and annually until last follow-up: modified Ashworth Scale, Reflex Scale, modified Rankin Scale and Rivermead Mobility Index. The ITB dosages were assessed after reaching steady state as well as annually until last follow-up. Results: The ITB device was implanted 13±6 (range 9-16) years after diagnosis of HSP on average. Severe spasticity was controlled in all patients by a mean baclofen dosage of 188±60 (range 145-230) µg per day at steady state post-implantation. The modified Ashworth Scale improved significantly from 3 (interquartile range [IQR] 3-3.25) to 1 (IQR 1-1.25; p=0.046), as did the Reflex Scale from 5 (IQR 4.75-5) to 3 (IQR 2.75-3; p=0.046) at steady state dosage of ITB. The modified Rankin Scale improved from 2 (IQR 2-2) to 1 (IQR 1-1.5; p=0.083) and the Rivermead Mobility Index remained 14 (IQR 13.5-14 pre-implantation, IQR 14-14 post-implantation; p=0.18). Post-implantation, spasticity improved for 2-3 years, followed by a stable phase of ambulatory and other mobility functions for 4-5 years. Thereafter, the maintenance or progressive loss of mobility depended on individual courses of the disease. No ITB-related severe side effects occurred. Discussion: Our data further support the role of ITB in the treatment of severe spasticity in patients with deteriorated walking performance suffering HSP. ITB therapy may initially improve spasticity and stabilize mobility functions for the first 6-8 years in patients with HSP.